Crescimento, transpiração e vulnerabilidade à restrição hídrica em plantas jovens de clones de Eucalyptus - Santos, Aline Ramalho dos (2023)
The availability of soil water is one of the main drivers of forest productivity. However, recent projections indicate that climatic extremes, such as severe droughts, are predicted for future decades, associated with global climate change, potentially affecting the development and permanence of tree species in natural environments. Therefore, the aim of this study was to determine the growth, transpiration and vulnerability to water restriction of three Eucalyptus clones. The thesis was structured in two chapters. Chapter 1 quantified the growth and actual transpiration rate of Eucalyptus urophylla x Eucalyptus grandis clones. The results indicated that the growth curves follow a model with a sigmoidal trend. Eucalyptus clones show differences in CO2 assimilation efficiency, where clone A211 reached the highest net photosynthetic rates. For the apparent quantum yield the best averages were observed for I144 and CO1407. Biomass production and partitioning were higher for clone I144 and A211. These differences stem from the efficiency with which plants can convert and assimilate light through photosynthesis. Regarding water use efficiency, clones A211 and CO1407 showed higher biomass yield per gram of transpired water. A gradual increase in water consumption of Eucalyptus clones was observed, where the maximum values were reached in the period in which the plants reached high leaf area values. The volume of water consumed at the end of 1689 accumulated degree-days was higher for clone I144. It was also verified that the expansion of the leaf area boosted transpiration and greater efficiency in the use of the balance of energy in the process of water loss from the plants. Chapter 2 aimed to characterize the hydraulic architecture and vulnerability of young Eucalyptus plants to drought, in order to predict responses to fluctuations in water availability. The results indicated that the evaluated Eucalyptus genetic materials are highly vulnerable to cavitation. The water transport capacity of the plants was significantly reduced, due to the systemic failure of the vascular system. It was also observed that the hydraulic compromise restricted the photosynthetic performance, the stomatal conductance and the transpiration of the plants during episodes of severe drought. In addition, it limited the heat dissipation and evaporative cooling processes of the leaves.